Pemberdayaan Masyarakat Melalui Pelatihan dan Pendampingan dalam Meningkatkan Ekonomi Masyarakat Desa - Muhammad Rifai Katili; Sitti Suhada; Lanto Ningrayati Amali (Univeristas Negeri Gorontalo, 2019)
Community empowerment can occur if the community itself can improve its own situation/condition and participate in becoming a reformer/motor driving agent in development. The goal that wants to be achieved in this activity is the realization of independent villages that uphold the local wisdom of the community as active participatory actors in an effort to improve the creative economy of the community. Special targets of activities, namely: (1) the increase in awareness of community business, especially in increasing agricultural activities and local culture of the community, (2) the improvement of the knowledge and skills of household businesses that are managed independently by utilizing natural resources. This method of activity is a workshop in the form of socialization, training and mentoring in the community intensively so that it achieves all the expected targets and outsiders, and through the implementation of this activity can improve the creative economy of the community.